Retaining repatriates: an exploratory study in portuguese companies - Martins, Dora (2014)
This study aims to understand the factors which may explain the retention of repatriates from companies acting within Portugal. These factors can be related either to the individual, or to the work, to the organisation or to non-working contexts. Eight companies located in Portugal have participated in this study. Several semi-structured interviews were done to 16 organizational representatives and to 28 repatriates. The obtained results show that the repatriates’ retention on the visited companies may be influenced by several categories of factors. We can conclude that it is (1) the good relation with the leadership, (2) the recognition of the performed job but, also (3) the seniority, (4) the age and the (5) depressed national job market. These are the major factors that emerge as relevant factors for the retention. Hence, there is not only one category of explaining determining factors for the retention decision, but there are several. These findings will be discussed in detail and implications and suggestions for future research will be proposed as well.